2010
DOI: 10.1039/c0cc00693a
|View full text |Cite
|
Sign up to set email alerts
|

Modification of DNA-templated conductive polymer nanowires via click chemistry

Abstract: DNA templated nanowires of a pentynyl-modified poly2-(2-thienyl)-pyrrole undergo functionalisation via"click chemistry" and retain their 1D-nanostructure and conductive properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…Co., and were used as received. Pentafluorophenyl acrylate (PFA) and 3‐azidopropylamine were prepared according to the methods reported in the literature …”
Section: Methodsmentioning
confidence: 99%
“…Co., and were used as received. Pentafluorophenyl acrylate (PFA) and 3‐azidopropylamine were prepared according to the methods reported in the literature …”
Section: Methodsmentioning
confidence: 99%
“…This method has been used to incorporate alkynyl groups to enhance the nucleation of subsequent Ag layers, 48 or to allow the functionalisation of the NWs by the copper-catalysed azide-alkyne Huisgen cycloaddition, 'click', reaction. 49 2 Structure of DNA-templated nanowires and the mechanism of templating The details of the mechanism of DNA-templating are of fundamental interest, but also have signicance for the major proposed applications of NWs as interconnects in electronic devices and as transducing elements in chemical sensors. In the case of interconnects, it is clearly desirable for the NWs to be uniform and continuous to attain the maximum possible conductivity.…”
Section: Conductive Polymersmentioning
confidence: 99%
“…[33] Additionally,t he DNA template can guide the polymerization of monomers to produce uniformly decorated materialst op rovidee venly spacedn ucleation sites for metal ion deposition to improveD NA wire properties. [34] Long DNA strandsc ontaining high copy numbers( up to 10 kbp) of short repeats equences (2-3 nucleotides)a re readily synthesised from 10-20 mer duplex oligonucleotides using isothermals lippage methods. [17,35] Although isothermal slippage has been shown to occur for 6-10 bp repeats such as telomeric sequences, [36] we have found that intermediate sized repeat sequences (4-40 nucleotides)a re most efficiently extended by thermalc ycling methods.…”
Section: Introductionmentioning
confidence: 99%